A study of factors causing cancellation or postponement of construction projects in the UAE - Al Khoori, Thuraya (2012)
This dissertation examines the factors that cause cancellation or postponement of construction projects within the UAE. Price fluctuation in the price of construction materials is one of the factors that have contributed to cancellation or postponement of projects in the UAE. This has motivated both contractors and developers to finish the projects on time. Additionally, inflation and economic instability has caused the UAE construction sector to experience financial difficulties. The objectives include: To outline the importance of the construction industry and the effects it has on the Abu Dhabi economy, analyze factors that result in postponement or cancellation of construction projects, identify various impacts of the cancellation or postponement and identify suitable mitigation measures. In order to attain these objectives, four different case studies were used which examines the effects of a number of factors on the UAE construction industry. In conclusion, from the information gathered, it is evident that the UAE construction has been impacted negatively by factors such as inflation, fluctuation in the price of construction materials, and poor management resulting in the cancellation or postponement of projects.